Pandemic insights: what COVID-19 has revealed about traditional rounding structure - Michael Czapka; Christopher Lehmann (Springer, 2023)
Abstract Due to social distancing policies and concerns over patient and provider safety, early in the COVID-19 pandemic many healthcare institutions temporarily converted to various, non-traditional rounding models. The abrupt and unprecedented change in workflow has enabled re-assessment of the reasons for the traditional rounding structures in medical education and comparison to newer strategies for rounding which have developed out of necessity during the pandemic. In this Perspectives article, we examine the positive and negative aspects of rounding models borne out of the pandemic and suggest aspects which may be carried forward, as well as future directions for research.